Microbiological and biochemical studies on chitinolytic enzymes and antitumor activity of chitinous hydrolysates - Amira Abood Abdeldaim Khalaf; Alaa Eldin Mahmoud Shawky Hosny; Azza Mohamed Abdelfattah; Hussein Shoaeb (Cairo : Amira Abood Abdeldaim Khalaf, 2010)
Isolation of different actinomycetes strains from marine sources and was screened for chitinolytic activity, the most potent one was Streptomyces champavatii for production of chitinase using liquid fermentation, the highest endo - and exochitinase yields were produced after 7 - days and 6 - days . Colloidal chitin was the suitable substrate for enzymes production with concentration 0.5 -1.75% (w\v) for exo - and endochitinase respectively
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Microbiology and Immunology
Issued also as CD
Keywords: Actinomycetes; Endochitinase; Exochitinase